The Blessingway Ceremony: Ritual, Nostalgic Imagination and Feminist Spirituality - Burns, Emily (Journal of religion and health, 2015)
There is an increasing interest in the role of spirituality on the experience of health, wellness and illness, as well as the role of spiritual practice in health care provision. For pregnancy and childbirth, this focus has tended to concentrate on hospital birth settings and care, and religious forms of spirituality. The blessingway ceremony can be described as an alternative baby shower, popular with home-birthing women. Its focus is woman-centred and draws on the power of ritual to evoke a spiritual experience for the pregnant host and her guests. This spirituality is experienced as a strong connection between women, their relationship with nature, and forged via the nostalgic imagination of women through time and space. This article will draw on data obtained in 2010 during doctoral fieldwork with 52 home-birthing women across eastern Australia and will examine the blessingway ceremony and its significance as a site of potential spiritual empowerment for pregnant and birthing women.